Fabrication of Porous Biochip Carrier Based on HDPE with Microbial Compatibility for Domestic Wastewater Treatment Using MBBR Technology - Huynh, Mai Duc; Minh, Nguyen Quang; Trung, Tran Huu; Cong, Do Van; Thai, Nguyen Thi; Minh, Nguyen Tien; Huyen, Dang Thanh; Nguyen, Minh Viet; Thu, Ngo Hong Anh; Son, Do Van; Giang, Nguyen Vu (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 1DO - 10.25073/2588-1140/vnunst.5849, 2026)
This study presents the development of a porous HDPE/PEO-based biochip carrier enhanced with maleic anhydride-grafted polyethylene (PEgMA) for domestic wastewater treatment using Moving Bed Biofilm Reactor (MBBR) technology. The incorporation of hydrophilic PEO and PEgMA improved microbial compatibility by enhancing hydrophilicity and surface interaction. The optimized carrier achieved a density of 0.61 g/cm³, 40.48% porosity, and pore sizes ranging from 50–500 µm. After 8 weeks of operation at Hung Yen Eye Hospital, the system achieved 99.8% ammonium removal and met national discharge standards (QCVN 14:2008/BTNMT). The study confirms the potential of HDPE/PEgMA/PEO carriers as high-efficiency, scalable solutions for sustainable domestic wastewater treatment using MBBR systems.